1 Avelumab in combination with and/or following chemotherapy vs chemotherapy in treatment-naive patients with ovarian cancer: biomarker analyses from the phase 3 JAVELIN Ovarian 100 trial. (13th November 2020) - Ledermann, J; Colombo, N; Oza, A; Fujiwara, K; Birrer, MJ; Randall, L; Poddubskaya, E; Scambia, G; Shparyk, YV; Lim, MC; Lim, MC; Sohn, J; et al.
Abstract : Introduction: In the JAVELIN Ovarian 100 trial (NCT02718417 ), avelumab (anti–PD-L1) in combination with chemotherapy or as maintenance did not improve progression-free survival (PFS) vs chemotherapy followed by observation in treatment-naive patients with epithelial ovarian cancer (EOC; hazard ratios [95% CI] were 1.14 [0.832, 1.565] and 1.43 [1.051, 1.946], respectively). The trial was terminated when prespecified futility boundaries were crossed at the interim analysis, and study treatment was subsequently discontinued. Here we report biomarker analyses. Methods: Women with stage III-IV EOC (post debulking/cytoreductive surgery or candidates for neoadjuvant chemotherapy) were randomized 1:1:1 to receive carboplatin/paclitaxel chemotherapy (6 cycles) followed by avelumab every 2 weeks as maintenance (CTx→Ave), chemotherapy + avelumab (10 mg/kg every 3 weeks) followed by avelumab every 2 weeks as maintenance (CTx+Ave→Ave), or chemotherapy followed by observation (CTx→O; control arm). The primary endpoint was PFS by blinded independent central review per RECIST version 1.1. Pretreatment tumor tissue was analyzed by immunohistochemistry (CD8 and PD-L1) and next-generation DNA and RNA sequencing. Results: 998 patients were randomized. Subgroup analyses based on PD-L1, CD8, and germline BRCA1/2 status did not identify subsets with clear PFS benefit in either avelumab arm vs control (table 1 ). Whole-exome and RNA sequencing analyses will be presented. Conclusions: In the JAVELIN Ovarian 100 trial, PD-L1, CD8, and germline BRCA1/2 status did not predict differential clinical benefit with the addition of avelumab to chemotherapy in treatment-naive patients with EOC.